2016
DOI: 10.5380/rel.v93i1.42690
|View full text |Cite
|
Sign up to set email alerts
|

The interpretation of Brazilian Portuguese bare singulars in neutral contexts

Abstract: The interpretation of Bare Singular count nouns (henceforth BS nouns) has been at the center of much debate in the literature on countability in Brazilian Portuguese. In this paper, we ad- dress the question whether BS nouns may only be interpreted as mass nouns or as names of kinds, or whether they may also be interpreted as object denoting nouns. It is generally agreed that BS nouns can be interpreted as names of kinds. Furthermore, Beviláqua and Pires de Oliveira (2014) show that BS nouns are interpreted as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 13 publications
(22 reference statements)
2
16
0
Order By: Relevance
“…Our results also show that naturally atomic bare nouns are highly unlikely to be associated with Volume (Measure reading) when a cardinal interpretation is available, in neutral contexts. Similar results were found by Lima & Gomes (2016). Following these authors, we claim that these results could be seen as the result of a cognitive bias effect and lexical statistics.…”
Section: Final Remarkssupporting
confidence: 89%
See 1 more Smart Citation
“…Our results also show that naturally atomic bare nouns are highly unlikely to be associated with Volume (Measure reading) when a cardinal interpretation is available, in neutral contexts. Similar results were found by Lima & Gomes (2016). Following these authors, we claim that these results could be seen as the result of a cognitive bias effect and lexical statistics.…”
Section: Final Remarkssupporting
confidence: 89%
“…Third, the volume answer is unlikely to be chosen when the cardinality answer is available for the BS in neutral contexts, 14 as shown by Lima & Gomes (2016) Two tentative hypotheses could explain the low acceptance of a volume interpretation for BS nouns. The first is the lexical statistics hypothesis, and the second is the cognitive bias hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous quantity judgments in Brazilian Portuguese have shown that count (colher 'spoon') and object mass nouns (mobília 'furniture') were more likely to be associated with the Number answer (99% and 97% of Number responses, respectively) while substance mass nouns (farinha 'flour') were more likely to be associated with the Volume answer (21% of Number responses) (cf. Lima and Gomes 2016). It is important to say that these results were obtained in tasks where count nouns appeared pluralized (Quem tem mais colheres?…”
Section: General Discussion (Studies 1 and 2)mentioning
confidence: 99%
“…Pires de Oliveira & Rothstein (2011) suggest that bare singulars in Brazilian Portuguese would not particularly favor a cardinal interpretation over a non-cardinal interpretation. In Lima & Gomes (2016) and Beviláqua et al (2016), it was suggested that the preference for cardinality over non-cardinal interpretations in neutral contexts in Brazilian Portuguese is due to the lexical frequency of bare singulars being interpreted with cardinal interpretation. As such, the preference for cardinality is not encoded in the semantics of the noun, but could be a pragmatic effect.…”
Section: General Discussion (Study 3)mentioning
confidence: 99%
“…For example, studies of Brazilian Portuguese have shown that this language allows bare singulars (bare count nouns in argument position) and thus does not fit the typology (cf. Lima & Gomes, ; Müller, ; Müller & Oliveira, ; Munn & Schmitt, ; Paraguassu & Müller, ; Pires de Oliveira & Rothstein, ; Schmitt & Munn, , among others).…”
Section: The Description Of Understudied Languages and The Advance Ofmentioning
confidence: 99%